THE RELATIONSHIPS BETWEEN PHYSICAL ACTIVITIES AND DYSMENORRHEA IN ADOLESCENT THE CITY OF BANDUNG - Rahayu, Kusila Devia; Kartika, Ira; Dayanti, Rina (Journal of Maternity Care and Reproductive Health, 2019)
Dysmenorrhea is a problem that often occurs in adolescents during menstruation. This study aimed to determine the relationship between physical activity and dysmenorrhea in adolescents in the city of Bandung. The study was a descriptive correlation study, with a cross-sectional approach. Samples were selected by the total sampling method, 68 female adolescents involved in this study. Physical activity was measured using a standard instrument, namely Baecke Physical Activity Scale and measurement of dysmenorrhea was measured using the Numeric Rating Scale pain scale. Data processing techniques used the Spearman Rank coefficient correlation. The results of the study revealed that there was a relationship between physical activity and dysmenorrhea (P = 0.000) and significance value sig <0.005. The value of the correlation coefficient was r = - 0.650 means there was a strong relationship between variables. Conclusion, there is a significant relationship between physical activity and dysmenorrhea in the city of Bandung. Health workers through the UKS program are expected to increase female physical activity through additional sports as a program to prevent dysmenorrhea.Keywords: Adolescence,  dysmenorrhea, Physical activity.